2018
DOI: 10.2174/1872312812666180625122810
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals Changes in Transporter Protein Abundance in Liver, Kidney and Brain of Mice by Pregnancy

Abstract: Protein abundance of drug transporters can be significantly changed particularly in the liver by pregnancy. These results will be helpful to understand pregnancy-induced changes in drug/xenobiotic disposition in the mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Targeted Proteomic Analysis of Hepatic DMETs by LC-MS/MS. Quantification of relative protein abundance of major DMETs in the liver tissues of CV and GF mice was done by quantitative LC-MS/MS proteomic analysis using methods previously described (Bhatt and Prasad, 2018;Liao et al, 2018;Prasad et al, 2018). For P450 enzymes, changes in protein levels of CYP2C37, CYP2C50, CYP2C54, CYP2D22, CYP2D40, CYP3A11, CYP3A16, and CYP3A41 were quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted Proteomic Analysis of Hepatic DMETs by LC-MS/MS. Quantification of relative protein abundance of major DMETs in the liver tissues of CV and GF mice was done by quantitative LC-MS/MS proteomic analysis using methods previously described (Bhatt and Prasad, 2018;Liao et al, 2018;Prasad et al, 2018). For P450 enzymes, changes in protein levels of CYP2C37, CYP2C50, CYP2C54, CYP2D22, CYP2D40, CYP3A11, CYP3A16, and CYP3A41 were quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative proteomics can selectively and precisely quantify BBB transporters, such as P-gp, BCRP, and MRPs. 34,94 Also, variable transporter expression plays a crucial role in the etiology and pathogenesis of different brain diseases such as Alzheimer's disease, epilepsy, Creutzfeldt-Jakob disease, and Parkinson's disease. For effective treatment of central nervous system disorders, a drug must reach a target site in the brain.…”
Section: Other Diseasesmentioning
confidence: 99%
“…In brain disorders, the effectiveness of drug therapy is often reduced because of the resistance, which is caused by increased expression of efflux transporters (eg, P‐gp) at the blood‐brain barrier (BBB). Quantitative proteomics can selectively and precisely quantify BBB transporters, such as P‐gp, BCRP, and MRPs 34,94 . Also, variable transporter expression plays a crucial role in the etiology and pathogenesis of different brain diseases such as Alzheimer's disease, epilepsy, Creutzfeldt‐Jakob disease, and Parkinson's disease.…”
Section: Impact Of Disease Conditions On Drug Disposition and The Potmentioning
confidence: 99%
“…Pregnancy improves the early entry of the cell cycle of hepatocytes, hepatic fat accumulation, and hepatocyte mitosis, which have positive effects on maternal liver regeneration following partial hepatectomy in mice (Lee et al, 2020). There are significant changes in protein abundance of major drug/xenobiotic transporters in the maternal liver of mice during pregnancy (Liao et al, 2018). It has been reported that early pregnancy enhances expression of progesterone (P4) receptor, P4‐induced blocking factor (Zhang et al, 2019), cyclooxygenase‐2, prostaglandin (PG) E synthase, PGF synthase (Yang, Han, et al, 2020), interferon‐stimulated genes (Yang, Li, et al, 2020), and interleukin (IL)‐5 (Yang et al, 2019) in the maternal liver during early pregnancy in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…There are significant changes in protein abundance of major drug/ xenobiotic transporters in the maternal liver of mice during pregnancy (Liao et al, 2018). It has been reported that early pregnancy enhances expression of progesterone (P4) receptor, P4-induced blocking factor (Zhang et al, 2019), cyclooxygenase-2, prostaglandin (PG) E synthase, PGF synthase (Yang, Han, et al, 2020), interferon-stimulated genes , and interleukin (IL)-5 (Yang et al, 2019) in the maternal liver during early pregnancy in sheep.…”
mentioning
confidence: 99%